2021
DOI: 10.5005/jp-journals-10071-23946
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Age-adjusted Charlson Comorbidity Index as a Predictor of Need for Invasive Mechanical Ventilation, Length of Hospital Stay, and Survival in COVID-19 Patients

Abstract: A bstract Background Multiple parameters may be used to prognosticate coronavirus disease-2019 (COVID-19) patients, which are often expensive laboratory or radiological investigations. We evaluated the utility of age-adjusted Charlson comorbidity index (CCI) as a predictor of outcome in COVID-19 patients treated with remdesivir. Materials and methods This was a single-center, retrospective study on 126 COVID-19 patients treated with remdesivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…All the clinical scores we used for prognosis stratification in our cohort (CCI, NEWS2 and CoLACD scores) proved to correlate with ICU admission and in-hospital mortality in patients without ASCVD, while only NEWS2 was correlated with ICU admission and death in patients with a history of ASCVD. Our results are in line with other studies, which reported that an age adjusted CCI is predictive for mortality and invasive mechanical ventilation [ 47 ], and NEWS2 score can identify inpatients deterioration [ 19 ]. The CoLACD score proved to be useful as a mortality predictor in COVID-19 patients [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…All the clinical scores we used for prognosis stratification in our cohort (CCI, NEWS2 and CoLACD scores) proved to correlate with ICU admission and in-hospital mortality in patients without ASCVD, while only NEWS2 was correlated with ICU admission and death in patients with a history of ASCVD. Our results are in line with other studies, which reported that an age adjusted CCI is predictive for mortality and invasive mechanical ventilation [ 47 ], and NEWS2 score can identify inpatients deterioration [ 19 ]. The CoLACD score proved to be useful as a mortality predictor in COVID-19 patients [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…The COVID-19 disease has affected millions of human beings and caused more death rates worldwide. Therefore, Shanbhag et al [ 30 ] have designed the ML-based mortality prediction model, which was applied to the clinical data set. Here, 961 data sets are worn for the preparation process, and 249 data sets are used as the testing procedure.…”
Section: Related Workmentioning
confidence: 99%
“…For this purpose, various scoring and evaluation systems have been used in many studies. Of these, the Charlson comorbidity index has been reported as an important prognostic marker (Bannay et al, 2016;Christensen et al, 2020;Imam et al, 2020;Shanbhag et al, 2021;Sabaz and Aşar, 2021). It is a simple and easy scoring system that evaluates the total comorbidity burden.…”
Section: Black Sea Journal Of Health Sciencementioning
confidence: 99%
“…In patients diagnosed with COVID-19; studies have been conducted to show the impact of clinical, demographic, laboratory, epidemiological and radiological characteristics on mortality (Li et al, 2020). Many descriptive observational studies have also found that patients with comorbidities are disproportionately affected by COVID-19 and are associated with poorer clinical outcomes (Christensen et al, 2020;Guan et al, 2020;Shanbhag et al, 2021). Therefore, comprehensive assessment of comorbidities for risk stratification of hospitalized patients with COVID-19 and accurate prediction of prognosis are important for clinical management and outcomes.…”
Section: Introductionmentioning
confidence: 99%